La Nausée Through Barthes: A Retroactive reading - Diklich-Newell, Thea (Romance eReview, 2017)
In his 1938 novel La Nausée, Jean-Paul Sartre proposed a re-examination of the physical world, centering around man’s relationship to society as well as his relationship to specific objects and the signs used to refer to those objects. For Sartre, these objects and our ways of referring to and interacting with them reveal deep-seeded social constructs that allow the individual and society as a whole to exist in a world that is, ultimately, absurd. In 1957, Roland Barthes published a collection of essays, including the piece “Myth Today,” entitled Mythologies. In this publication, Barthes examined the construct of signs and their meanings, and went on to examine their role in creating myths, which for him are equally essential to dealing with the absurdity of human existence. These two texts are attempts to understand man’s relationship to language and its role in shaping society. The author of this article proposes a reading of Sartre’s La Nausée through the lens of Barthes Mythologies, with the intent of revealing any significant agreement, disagreement, development or abandonment of themes that will highlight the way two of the 20th century’s most prominent thinkers approached the subject of society and human existence through language and its role in contemporary society.